Prognostic factors of the results of cardiopulmonary resuscitation in a cardiology hospital - Timerman,Ari (2001)
OBJECTIVE: To analyze the early and late results of cardiopulmonary resuscitation in a cardiology hospital and to try to detect prognostic determinants of both short- and long-term survival. METHODS: A series of 557 patients who suffered cardiorespiratory arrest (CRA) at the Dante Pazzanese Cardiology Institute over a period of 5 years was analyzed to examine factors predicting successful resuscitation and long-term survival. RESULTS: Ressuscitation maneuvers were tried in 536 patients; 281 patients (52.4%) died immediately, and 164 patients (30.6%) survived for than 24 hours. The 87 patients who survived for more than 1 month after CRA were compared with nonsurvivors. Coronary disease, cardiomyopathy, and valvular disease had a better prognosis. Primary arrhythmia occurred in 73.5% of the >1-month survivor group and heart failure occurred in 12.6% of this group. In those patients in whom the initial mechanism of CRA was ventricular fibrillation, 33.3% survived for more than 1 month, but of those with ventricular asystole only 4.3% survived. None of the 10 patients with electromechanical dissociation survived. There was worse prognosis in patients included in the extreme age groups (zero to 10 years and 70 years or more). The best results occurred when the cardiac arrest took place in the catheterization laboratories. The worst results occurred in the intensive care unit and the hemodialysis room. CONCLUSION: The results in our series may serve as a helpful guide to physicians with the difficult task of deciding when not to resuscitate or when to stop resuscitation efforts.